Fluctuations of Otoacoustic Emissions and Medial Olivocochlear Reflexes: Tracking One Subject over a Year - Malgorzata Pastucha; W. Wiktor Jedrzejczak (Audiology Research, 2022)
The purpose of the study was to measure the variability of transiently evoked otoacoustic emissions (TEOAEs) and the medial olivocochlear reflex (MOCR) over a long period of time in one person. TEOAEs with and without contralateral acoustic stimulation (CAS) by white noise were measured, from which MOCR strength could be derived as either a dB or % change. In this longitudinal case study, measurements were performed on the right and left ears of a young, normally hearing adult female once a week for 1 year. The results showed that TEOAE level and MOCR strength fluctuated over the year but tended to remain close to a baseline level, with standard deviations of around 0.5 dB and 0.05 dB, respectively. The TEOAE latencies at frequencies from 1 to 4 kHz were relatively stable, with maximum changes ranging from 0.5 ms for the 1 kHz band to 0.08 ms for the 4 kHz band. TEOAE levels and MOCR strengths were strongly and negatively correlated, meaning that the higher the TEOAE level, the lower the MOCR. Additionally, comparison of fluctuations between the ears revealed positive correlation, i.e., the higher the TEOAE level or MOCR in one ear, the higher in the second ear.